Mutation of a single residue in the ba(3) oxidase specifically impairs protonation of the pump site - von Ballmoos, Christoph (Proc Natl Acad Sci U S A, 2015)
The ba(3)-type cytochrome c oxidase from Thermus thermophilus is a membrane-bound protein complex that couples electron transfer to O(2) to proton translocation across the membrane. To elucidate the mechanism of the redox-driven proton pumping, we investigated the kinetics of electron and proton transfer in a structural variant of the ba(3) oxidase where a putative “pump site” was modified by replacement of Asp372 by Ile. In this structural variant, proton pumping was uncoupled from internal electron transfer and O(2) reduction. The results from our studies show that proton uptake to the pump site (time constant ∼65 μs in the wild-type cytochrome c oxidase) was impaired in the Asp372Ile variant. Furthermore, a reaction step that in the wild-type cytochrome c oxidase is linked to simultaneous proton uptake and release with a time constant of ∼1.2 ms was slowed to ∼8.4 ms, and in Asp372Ile was only associated with proton uptake to the catalytic site. These data identify reaction steps that are associated with protonation and deprotonation of the pump site, and point to the area around Asp372 as the location of this site in the ba(3) cytochrome c oxidase.